2017
DOI: 10.1371/journal.pone.0170733
|View full text |Cite
|
Sign up to set email alerts
|

Association of Myopic Deformation of Optic Disc with Visual Field Progression in Paired Eyes with Open-Angle Glaucoma

Abstract: PurposeThe influence of myopia on glaucoma progression remains unknown, possibly because of the multifactorial nature of glaucoma and difficulty in assessing a solo contribution of myopia. The purpose of this study is to investigate the association of myopia with visual field (VF) progression in glaucoma using a paired-eye design to minimize the influence of confounding systemic factors that are diverse among individuals.MethodsThis retrospective study evaluated 144 eyes of 72 subjects with open-angle glaucoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…The present findings demonstrating a significant association between the optic disc tilt and the number of LC defects are in accordance with this hypothesis. The present results further confirmed the findings of our recent studies, where we described the association of optic disc tilt with the severity 18 and progression 19 of VF defects in myopic glaucoma and provided evidence that optic disc tilt affects VF defects by way of an increased number of temporal LC defects. In addition, a previous study demonstrated development of PCS from the early stage of glaucoma in highly myopic eyes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present findings demonstrating a significant association between the optic disc tilt and the number of LC defects are in accordance with this hypothesis. The present results further confirmed the findings of our recent studies, where we described the association of optic disc tilt with the severity 18 and progression 19 of VF defects in myopic glaucoma and provided evidence that optic disc tilt affects VF defects by way of an increased number of temporal LC defects. In addition, a previous study demonstrated development of PCS from the early stage of glaucoma in highly myopic eyes.…”
Section: Discussionsupporting
confidence: 93%
“…15e17 The association between myopia and glaucoma has been studied intensively, and it gradually becomes clear that myopia influences glaucomatous damage not through refractive error itself, but through deformation of the parapapillary region. 18,19 Myopic eyes present characteristic deformations of the parapapillary region, including optic disc tilt and torsion and parapapillary atrophy. Because LC is a deep component of the optic nerve head, it is reasonable to think that the LC, too, is deformed in myopic eyes and that it affects axonal injury in glaucoma.…”
mentioning
confidence: 99%
“…is may cause distortion of the optic nerve structure at an early age, [15,16], and exert a tensile or shearing stress on the axons passing through the lamina pores. Long-standing stress from an early age could generate axonal damage by itself [17] or increase the susceptibility of the axons to IOP-related mechanical stress [18]. is could explain why eyes with c-zone PPA have an RNFL defect of similar extent at an earlier age compared to those with β-zone PPA.…”
Section: Discussionmentioning
confidence: 99%
“… 21 A recent study found that myopia might worsen glaucomatous visual field impairment via myopic optic disk deformation, rather than directly via refractive error or axial length. 22 In addition to this glaucoma-susceptible eye condition, long-time computer use might interactively increase the risk of glaucoma. Myopia might also be associated with a bias toward educational factors that lead to differences in lifestyles or working habits, as intelligence and education appear to be important triggers of this condition.…”
Section: Discussionmentioning
confidence: 99%